The construction of the consumer from habitus and reflexivity - Rivera, Juan Jesús (Revista Bricolaje, 2022)
Consume to live, live to consume, discard, repeat and accept that consumption results in the most diverse forms of daily interaction in society. There are, however, two ways of conceiving consumption that currently require particular attention, one, which, on the one hand, refers to the internalization of the articulated structure from the beginning of our life trajectory through habitus; another that, for its part, has the power to conceive the environment, life projects, the past, present, and future, using the internal conversations that reflexivity produces. The following article gives an account of the relationship between habitus and reflexivity for the constitution of two ideal types of consumption.